Caspofungin as secondary antifungal prophylaxis and subsequent maintenance antifungal prophylaxis therapy in hematological malignancy patients - Liu, Mingjuan (Int J Clin Exp Med, 2015)
Aim: This study aimed to investigate the efficacy and safety of caspofungin as secondary antifungal prophylaxis (SAP) and subsequent maintenance therapy for SAP in hematological malignancy patients. Methods: Forty four patients receiving caspofungin for SAP and 43 patients not receiving any SAP agents during their subsequent chemotherapy or HSCT were reviewed retrospectively. The clinical characteristics and diagnosis were analyzed according to the diagnostic criteria for IFD. Results: The recurrence rate of IFD in 44 patients with caspofungin for SAP was 9.1% (4/44), which was much lower than that in 43 patients without SAP (9.1% vs 46.5%, P = 0.000). Patients with SAP had lower recurrent IFD-related mortality than that without SAP (12.5% vs 55.6%, P = 0.131). Among the 44 patients with SAP, caspofungin continued as maintenance antifungal prophylaxis therapy in 18 patients after neutropenia and oral medication became possible, while voriconazole in 14 patients and itraconazole in 12 patients. The recurrent IFD occurred in 2, 1, 1 patient respectively. There was no statistical difference in recurrence rates among different maintenance antifungal prophylaxis therapies (P = 0.922). No severe adverse events were observed during SAP treatment. Conclusions: Caspofungin is effective and safe to prevent IFD recurrence in hematological malignancy patients undergoing chemotherapy or HSCT. A subsequent maintenance antifungal prophylaxis therapy of oral voriconazole or itraconazole instead of caspofungin after caspofungin as SAP during neutropenia is as effective as caspofungin given constantly.